Interactive Investigations - clint(3, (Bkatharines; bourne(3, (Bjanes; sunley(3, (Bchriss (London Harper collins, 2006)
help your pupils think like scientists with astep by step interactive guide to science investigations
age 5-6
age3-4
pentium processor(3, (Bwindows 98/me/nt/2000(3, (B64 mb ram (3,(Bhigh colour(3, (B75 mb hard disc spaces
1 2
Keywords: science -- investigations -- MPL; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs